Examination of promotive and protective effects on early adolescent prosocial behavior through a bioecological lens - Bates, Elizabeth J. S.; Berny, Lauren M.; Ganiban, Jody M.; Natsuaki, Misaki N.; Neiderhiser, Jenae M.; Shaw, Daniel S.; Leve, Leslie D. (Frontiers in Psychology, 2023)
Prosocial behavior during childhood has been associated with numerous positive developmental and behavioral outcomes in adolescence and adulthood. Prosocial behavior, which includes cooperation and helping others, develops within a bioecological context.Considering it through such a lens enhances the understanding of the roles of different bioecological factors in its development. Using data from a longitudinal study of adopted children and children reared with their biological parents, this paper examined if positive aspects of a child's bioecological system at age 7 predict prosocial behavior in early adolescence (age 11), and whether these bioecological factors could offset risk due to biological family psychopathology and/or maternal prenatal substance use. The analyses incorporated variables from different levels of Bronfenbrenner's bioecological model (the individual, microsystem, exosystem, and macrosystem) and examined the promotive, and potentially protective, effect of each contextual factor, while also considering their interplay with biological family psychopathology and prenatal substance use. Results from linear regression models indicated that the microsystem variable of parental warmth at age 7 had a promotive effect on age 11 prosocial behavior. Further, in addition to its main effect, parental warmth was protective against maternal substance use during pregnancy when children were raised with their biological parent(s). Household type (biological family) and biological family internalizing psychopathology were the only other significant predictors in the model, with each associated with lower prosocial behavior at age 11. Study results extend prior work on the benefits of parental warmth on child outcomes by employing a strength-based, bioecological approach to the development of prosocial behavior during early adolescence and examining "for whom" the effects of parental warmth are most protective.